Effect of modified atmosphere on storage life of purple passionfruit and red tamarillo : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Horticultural Science at Massey University - Pongjaruvat, Wattana (Massey University, 2007)
This study investigates methods to improve storage life of purple passionfruit (Passiflora edulis Sims) and tamarillo (Cyphomandra betacea (Cav.) Sendt). For passionfruit, the main problem for export and storage is shrivelling whereas for tamarillo the quality of the stem is a key factor in export standards. Eating quality of passionfruit was best described by the titratable acidity (TA) and the soluble solids content (SSC) with the optimal eating flavour found at an SSC/TA ratio between 10-11. Wax coating, ethylene scavenging, and modified atmosphere packaging (MAP) were assessed as tools to improve storage life. MAP with varying oxygen transmission rates (OTR at 5°C; 854, 1437, 2347 and 3089 ml m-2 day-1) were compared to the standard packaging in a cardboard box during storage at the commercial temperature of 8°C. Fruit quality was measured after 20, 28, and 42 days of storage with and without seven days of shelf life at 20°C in the same packaging as during storage. Waxing did not improve the quality of the fruit. MAP prevented shrivelling but in the packaging with lower OTR (854 - 1437 ml m-2 day-1) unacceptable external defects developed. Fruit quality in the packaging with the higher OTR (2347 - 3089 ml m-2 day-1) was similar except for the development of off-flavours in the packaging with an OTR of 2347 ml m-2 day-1 during shelf life possibly due to the high ethylene accumulation since the addition of an ethylene scavenger in a second trial eliminated the off-flavour development. The highest OTR MAP is the best option for long term storage. The second highest OTR MAP could be used providing an ethylene scavenger is added. To extend the storage life of tamarillo, two MAP options (OTR at 5°C; 1437 and 3089 ml m-2 day-1) were compared to the standard packaging in a cardboard box with polyliner as well as the effect of adding clove oil releasing sachets. All fruit were stored at 4°C for 56 days and fruit and stem quality was measured fortnightly with and without three days of shelf life at 20°C. MAP delayed the development of stem yellowing, which was related to chlorophyll degradation, but did not improve fruit quality and increased stem blackening and bleeding in the locule, especially when clove oil was added. Blackening was related to polyphenol oxidase activity and was aggravated by clove oil or by injury (e.g. disruption of cellular membranes) due to lower O2, higher CO2 and higher ethylene concentrations. Thus, for the two films tested, MAP with or without the addition of clove oil offered no advantages over conventional air storage.
Keywords: Storage; Passion fruit; Tamarillos